Efforts to Understand and Manage Acceptance of Change in the New Normal Era - Diah Ananda Kharisma; Nuri Aslami (Journal of Indonesian Management, 2022)
This research is planned to demonstrate with the ultimate goal of Understanding and Managing Changes in the New Normal Era. The world is currently unequal after slumping due to the incomparable Corona virus outbreak, causing many changes in the movement of almost every form of human life and the world. While the procedure is to obtain information through writing research, this study uses a qualitative descriptive strategy. The technique used to understand and monitor the identification of progress in the new typical period is a consequence of this new normal era. In the new normal period, to make and energize the many adjustments in the new normal era..